2016
DOI: 10.1016/j.idcr.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a Carbapenem-resistant Klebsiella pneumoniae carrying bla OXA-48 , bla VIM-2 , bla CMY-2 and bla SHV- with high dose combination of imipenem and amikacin

Abstract: We describe a case of 58-year-old man with septic shock due to Carbapenem-resistant Klebsiella pneumoniae (CR-Kp) bloodstream infections (BSI) who was successfully treated with a high dose association of amikacin and imipenem combined with continuous venovenous hemodiafiltration (CVVHDF).A Klebsiella pneumoniae (Kp) was isolated from the catheter culture and from two blood samples, drawn from the catheter before removal and from a peripheral vein. The Kp was intermediate to Amikacin (MIC = 16 μg/ml) and was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Therefore, a serious challenge of anti-infection therapy for CRE has been raised in clinical practice. Studies have revealed that compared to use carbapenems antibiotics alone, in the combination of carbapenems with other antibacterial agents such as tigecycline or polymyxin [ 25 – 28 ], amikacin [ 29 ] or fosfomycin [ 30 ] can considerably improve the outcomes of patient with CR-KP infection. Laurent adopted a combined pharmacotherapy regimen of dual carbapenems to provide a new approach in the treatment of CRE-induced infections [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a serious challenge of anti-infection therapy for CRE has been raised in clinical practice. Studies have revealed that compared to use carbapenems antibiotics alone, in the combination of carbapenems with other antibacterial agents such as tigecycline or polymyxin [ 25 – 28 ], amikacin [ 29 ] or fosfomycin [ 30 ] can considerably improve the outcomes of patient with CR-KP infection. Laurent adopted a combined pharmacotherapy regimen of dual carbapenems to provide a new approach in the treatment of CRE-induced infections [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 3/7 (42.8%) patients treated with this regimen achieved a clinical cure and survived. However, the addition of amikacin to a carbapenem, when there is susceptibility to amikacin, achieved better outcomes, with 3/4 (75%) patients with OXA-48 bloodstream infections treated with this regimen surviving (27,66). Colistin has been used in combination with both tigecycline and fosfomycin in six and four patients, respectively, in a large retrospective case series by Navarro-San Francisco et al which documented survival rates of 5/6 (83%) and 3/4 (75%) (27).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Aminoglycoside antibiotics including amikacin, gentamicin, kanamycin, streptomycin, and tobramycin alongside carbapenems such as meropenem/imipenem represent valid combination treatment therapies yielding synergistic effects for infections caused by carbapenem resistant Enterobacteriaceae (CRE) (Hajjej et al ., 2016; Terbtothakun et al ., 2021). The presence of multiple aminoglycoside genes encoding aminoglycoside-modifying enzymes (AMEs) among all three pOXA-48 AMR variants may prevent synergistic therapies involving both carbapenems and aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%